PD-L1+MDSCs are increased in HCC patients and induced by soluble factor in the tumor microenvironment - Iwata, Tomoaki; Kondo, Yasuteru; Kimura, Osamu; Morosawa, Tatsuki; Fujisaka, Yasuyuki; Umetsu, Teruyuki; Kogure, Takayuki; Inoue, Jun; Nakagome, Yu; Shimosegawa, Tooru (Scientific reports, 2016)
Myeloid-derived suppressor cells (MDSCs) could have important roles in immune regulation, and MDSCs can be induced in patients with various malignant tumors. The immune-suppressive functions of MDSCs in hepatocellular carcinoma (HCC) patients have not been clarified. Therefore, we tried to analyze the biological significance of MDSCs in HCC patients. We quantified PD-L1 + MDSCs of HCC patients in various conditions by using multi-color flow cytometry analysis. PBMCs from HCC patients contained significantly higher percentages of PD-L1 + MDSCs in comparison to those from healthy subjects ( p < 0.001). The percentages of PD-L1 + MDSCs were reduced by curative treatment for HCC ( p < 0.05), and the percentages of PD-L1 + MDSCs before treatment were inversely correlated with disease-free survival time. After we cocultivated PBMCs and several liver cancer cell lines in a transwell coculture system, the percentages of PD-L1 + MDSCs were significantly increased compared with control ( p < 0.05). The expression of M-CSF and VEGFA was higher in the cell lines that strongly induced PD-L1 + MDSCs. Peripheral blood from HCC patients had significantly higher percentages of PD-L1 + MDSCs in comparison to those of healthy subjects, and the percentages of PD-L1 + MDSCs were reduced by HCC treatment, suggesting that we might use PD-L1 + MDSCs as a new biomarker of HCC.